Article Argument in Abstracts: A Comparative Discourse Study Between Indonesian-Based and Refereed Journals in Islamic Studies - Shella Monica; Safnil Arsyad (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Although there have been studies on the ways writers argue for the importance of their work in their journal article abstracts, such studies on journal article abstracts in the field of Islamic studies have never been conducted. This is important because authors from different fields use different rhetorical styles and linguistic features in their journal articles, such as in their abstracts. The purpose of this study is to look into the argument strategy used in journal article abstracts that are published in local and refereed journals in the field of Islamic studies. For this study, 60 abstracts (i.e., 20 from Indonesian-based journals, 20 from Indonesian-based refereed journals, and 20 from international refereed journals) in Islamic studies were selected and analyzed. The findings indicate that, in terms of abstract length, the three groups of articles are not significantly different; however, in terms of the appearance of Move 1 (introduction, background, or setting) and article justification argument types, they are different. The articles published in the two groups of reputable journals (Indonesian-based and International Refereed Journals) are similar but different from those in Indonesian-based journals. This implies that local journal authors should modify their rhetorical and argumentative styles in their abstracts to match those found in reputable journals, thereby improving the quality of the abstracts.